COMMUNITY STRUCTURE OF BENTHIC FORAMINIFERA IN EASTERN WATERS OF SEGARA ANAK LAGOON IN CILACAP - Tjahjo Winanto; Petrus Hary Tjahja; Amron Amron; Taufan Harisan; Hendrayana Hendrayana (SEAMEO BIOTROP, 2022)
Benthic foraminifera are types of organisms that are sensitive to environmental changes, so they are often used as a bioindicator for aquatic environmental conditions. The purpose of this study was to determine the community structure of benthic foraminifera community, sediment types and the relationship between the abundance of foraminifera with the sediment types in the eastern waters of Segara Anakan Lagoon in Cilacap. Method used in this study was a survey method. Samples were taken by using random sampling method. The study was conducted at 5 stations with 3 repetitions. Laboratory observations carried out included the types and numbers of benthic foraminifera. Community structure of foraminifera among stations were analyzed using one-way ANOVA, while the relationship between community structures and water quality parameters was analyzed using Pearson correlation. The results showed that in the the eastern waters of Segara Anakan Lagoon there were 58 species of foraminifera which abundance ranged from 532 ind/m2 to 927 ind/m2. The diversity index of foraminifera was in the medium to high diversity categories. The uniformity index of foraminifera was in the high uniformity in a stable community. The dominance index of foraminifera was in the low category. The sediment types was fine sand, medium sand and coarse sand. The relationship between the abundance of foraminifera with the sediment types was strong with high R values (0.763-0.809).